Konseptualisasi Awal Framework Literasi Etis KAA untuk Siswa SD: Analisis Perspektif Guru dan Orang Tua di SDN 023 Palembang - Adelin, Adelin; Hartati, Eka; Everhard Riwurohi , Jan (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The rapid development of Coding and Artificial Intelligence (AI) technology has brought new challenges to the world of education, especially related to the importance of instilling ethical literacy from an early age. This study aims to develop an initial framework for AI ethical literacy that is appropriate for elementary school students by analyzing the perspectives of teachers and parents at SDN 023 Palembang. Through an exploratory qualitative approach, this study collected data from in-depth interviews with 5 teachers (3 class teachers and 2 curriculum developers) and 10 parents/guardians of students, as well as a literature study of previous research related to ethical literacy in the use of AI. The research findings reveal several key needs, including: (1) integration of digital ethics materials into the existing curriculum, (2) practical and contextual teacher training, (3) creative learning methods based on stories and games, and (4) active involvement of parents in the learning process. Based on these findings, this study produces a draft framework of 4 pillars that cover aspects of curriculum, teacher training, teaching methods, and collaboration with parents. Although still hypothetical and requiring further validation testing, this framework provides an important foundation for the development of ethical KAA education at the elementary level. The implications of this study are not only relevant for the development of school policies, but also provide theoretical contributions to the discussion on digital literacy for early childhood. Keywords: framework, artificial intelligence, coding, ethical literacy, elementary education.